The Impact of prostate – Specific Antigen Density In Predicting Prostate Cancer - Abdul-Kareem Sh. Al-Khafaji; Baha'a-Eladeen A. Al-Mujammaey (Diyala Journal of Medicine, 2019)
The objective of this study is to evaluate the impact of prostate-specific antigen density ( PSDA ) when serum levels of prostate-specific antigen ( PSA ) are less than 10 ng\ml in predicting prostate cancer. We retrospectively analyzed 134 patients who underwent trans rectal ultrasound ( TRUS )-guided prostate biopsies according to Cooner's algorithm. Histopathological examination revealed prostate cancer ( PCa ) in 22 ( 16% ) and begin prostatic hypertrophy ( BPH ) in 112 ( 84% ) patients.